2022
DOI: 10.3390/pathogens11121525
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii in Dogs and Cats from Portugal: Serological and Molecular Analysis

Abstract: Dogs and cats are potential sources of infection for some zoonotic diseases such as Q fever, caused by Coxiella burnetii, a multiple host pathogen. Q fever outbreaks in dogs and cats have been related with parturition and abortion events, and ticks have a potential role in the transmission of this pathogen. This study aimed to screen for C. burnetii in dogs and cats, and in ticks collected from infested animals. An observational descriptive study was conducted in Portugal at two time points nine years apart, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In Portugal, only one wild mammal molecular prevalence study has been performed, but red deer and wild boar were negative to C. burnetii [ 6 ]. Other studies performed in Portugal have reported Q fever in domestic ruminants [ 6 , 37 , 38 , 39 , 40 ], dogs and cats [ 41 ], and humans [ 42 , 43 , 44 , 45 ]. Nevertheless, this study is the first report of C. burnetii antibodies in red deer and wild boar in east–central Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal, only one wild mammal molecular prevalence study has been performed, but red deer and wild boar were negative to C. burnetii [ 6 ]. Other studies performed in Portugal have reported Q fever in domestic ruminants [ 6 , 37 , 38 , 39 , 40 ], dogs and cats [ 41 ], and humans [ 42 , 43 , 44 , 45 ]. Nevertheless, this study is the first report of C. burnetii antibodies in red deer and wild boar in east–central Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…An observational descriptive study was conducted in Portugal at two time points nine years apart, 2012 (29 cats) and 2021 (47 cats). Sera obtained from dogs and cats (total 294 sera) were tested for C. burnetii antibodies using a commercial ELISA adapted for multi-species detection; whereas a 17.2% prevalence was found among cats in 2012, when a higher percentage of animals from rural areas were analyzed, no positive cats were detected in 2021 [41]. Moreover, a molecular survey on reproductive tissues and/or endometrial swabs from 107 cats detected no positive cats [41].…”
Section: Epidemiological Surveys In Catsmentioning
confidence: 99%
“…ELISA is able to detect both anti-phase I and II antibodies, and is sensitive but laborious [79]. Commercial kits are available for the diagnosis of Q fever in humans and farm animals, but not for cats and dogs; therefore, the test has to be adapted to these investigated animal species [30,33,[38][39][40][41]43].…”
Section: Diagnosismentioning
confidence: 99%
“…The risk of close contact between humans and wild animals is relatively low, but when pet animals are considered, this risk is much higher. The paper of Anastàcio et al [ 9 ] showed that the monitoring of C. burnetii infections in companion animals is an important tool that may be used to prevent human outbreaks, considering the zoonotic potential of owners and veterinarians in contact with infected animals. The importance of proper surveillance was also highlighted in the paper of Pappa et al [ 10 ] on leishmaniasis, which is a neglected tropical disease affecting humans and domesticated animals, with high mortality in endemic countries.…”
mentioning
confidence: 99%